On a New Modification of Baskakov Operators with Higher Order of Approximation - Ivan Gadjev; Parvan Parvanov; Rumen Uluchev (Mathematics)
A new Goodman–Sharma-type modification of the Baskakov operator is presented for approximation of bounded and continuous functions on <semantics>[0,<mspace width="0.166667em"></mspace>∞)</semantics>. We study the approximation error of the proposed operator. Our main results are a direct theorem and strong converse theorem with respect to a related K-functional. Both theorems give complete characterization of the uniform approximation error in means of the K-functional. The new operator suggested by the authors is linear but non-positive. However, it has the advantage of a higher order of approximation compared to the Goodman–Sharma variant of the Baskakov operator defined in 2005 by Finta. The results of computational simulations are given.